2018
DOI: 10.1155/2018/9845075
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antibiofilm Activities of Nonpolar Extracts of Allium stipitatum Regel. against Multidrug Resistant Bacteria

Abstract: The present study assessed the in vitro antibacterial and antibiofilm potential of hexane (ASHE) and dichloromethane (ASDE) extracts of Allium stipitatum (Persian shallot) against planktonic cells and biofilm structures of clinically significant antibiotic resistant pathogens, with a special emphasis on methicillin-sensitive Staphylococcus aureus (MSSA), methicillin-resistant S. aureus (MRSA), and emerging pathogens, Acinetobacter baumannii and Stenotrophomonas maltophilia. Antibacterial activities were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 30 publications
1
8
0
1
Order By: Relevance
“…At the concentrations tested in biofilm assay, PYED-1 did not affect planktonic growth (data not shown). Several studies demonstrated that novel classes of antimicrobial compounds inhibit S. maltophilia biofilm formation [28][29][30][31][32][33]. In further support of this, our results showed that PYED-1 at 64 µg/mL significantly inhibited S. maltophilia biofilm formation on a polystyrene abiotic surface.…”
Section: Effects Of Pyed-1 On the Formation Of S Maltophilia Biofilmsupporting
confidence: 85%
“…At the concentrations tested in biofilm assay, PYED-1 did not affect planktonic growth (data not shown). Several studies demonstrated that novel classes of antimicrobial compounds inhibit S. maltophilia biofilm formation [28][29][30][31][32][33]. In further support of this, our results showed that PYED-1 at 64 µg/mL significantly inhibited S. maltophilia biofilm formation on a polystyrene abiotic surface.…”
Section: Effects Of Pyed-1 On the Formation Of S Maltophilia Biofilmsupporting
confidence: 85%
“…For example, the biofilm inhibition properties of A. sativum, A. stipitatum , A . orientale and A. porrum have been documented [ 19 , 20 , 21 , 22 ]. The inhibition of bacterial efflux pumps has also been suggested as a strategy to inhibit biofilm formation [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our earlier study, we identified dichloromethane extract of Allium stipitatum or Persian shallot, popularly known as “Mooseer”, a wild edible plant mostly found in the cold mountains of central, south, and western Iran, some provinces of Turkey, and central Asia, to exhibit strong antimicrobial and wound-healing activity [20,21,22,23,24]. Pyridine- N -oxide alkaloids and analogs of disulfides from A. stipitatum were reported to possess moderate to strong antibacterial activity against MDR S. aureus , Mycobacterium tuberculosis , Escherichia coli , and Klebsiella and Proteus species [25,26].…”
Section: Introductionmentioning
confidence: 99%